PERAN KEPALA SEKSI (KASI) PELAYANAN TERHADAP PELAYANAN PUBLIK DI DESA KRAMATLABAN (STUDI ANALISIS DESKRIPTIF DI DESA KRAMATLABAN KECAMATAN PADARINCANG KABUPATEN SERANG PROVINSI BANTEN) - Lina Marlina; Rai Robbi Rafsanjani (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2024)
ABSTRACT The role of the Service Section Head (KASI) towards Public Services in Kramatlaban Village, to find out the Barriers to the Service Section Head (KASI) towards Public Services in Kramatlaban Village, and to find out the Strategy of the Service Section Head (KASI) towards Public Services. This research uses qualitative research methods with the data analysis technique used, namely descriptive qualitative. The data collection techniques used were observation, interviews and documentation. The subjects of this research were the Kramatlaban Village Head, the Kramatlaban Village Secretary, the Kramatlaban Village Service Section Head (KASI), and the Kramatlaban Village community. The research results show that the role of the Service Section Head (KASI) and other village officials in Kramatlaban village is very good in terms of serving or carrying out their duties as village officials who are ready to help the Kramatlaban village community with correspondence needed by the community. And the strategy used for the community is providing guidance to the community either through RT and RW or recitation assemblies, explaining individually the importance of personal identity (Resident Identification Card and Family Card), disseminating service information through the Kramatlaban Village Resident whatsapp group.